The Feminist encyclopedia of French literature - Sartori, Eva Martin (Gale virtual reference library, 1999)
Provides extensive information about French women writers and the world in which they lived. Spans French literature from the Middle Ages to the present and covers those writers who lived and worked mainly in France.